Youthification across the metropolitan system: Intra-urban residential geographies of young adults in North American metropolitan areas. (October 2019) - Moos, Markus; Filion, Pierre; Quick, Matthew; Walter-Joseph, Robert
Abstract: The youthification hypothesis posits that young adult geographies are highly centralized, particularly in metropolitan regions with gentrified, amenity-rich downtowns successful in the knowledge economy. While prior studies have empirically substantiated centralized young adult geographies, none have considered intra-urban variations and linked these empirically to metropolitan-specific characteristics. Focusing on young adults aged 25 to 34 across 57 metropolitan regions in the United States and Canada with populations over one million, this study investigates how the residential geographies of young adults vary within and between metropolitan regions. Young adult geographies are analyzed via generalized additive models with cubic spline smoothing. Economic, housing, urban form, and demographic characteristics are compared between regions with different types of young adult geographies. Results show youthification to be widespread; young adult clusters exist in the downtowns of 56 metropolitan regions, with 31 regions having one downtown-focused young adult cluster and 25 regions having a multi-cluster profile. Only one region had a scattered profile with no clusters. Regions with a single centrally-located young adult profile had greater employment in the quaternary sector, higher public transit mode shares, fewer single-detached homes, and lower employment in manufacturing than those with multiple clusters. The study contributes to understanding the ways in which the residential geographies of specific age groups are shaped by aggregate characteristics of cohorts and the existing urban structures. Highlights: Investigates how residential geographies of young adults vary within and between metropolitan regions in the US and Canada. Young adult geographies are analyzed via generalized additive models with cubic spline smoothing. Metropolitan specific characteristics are compared between regions with different types of young adult geographies. Young adult clusters exist in 56 metropolitan regions; 31 regions have one cluster and 25 regions have multiple clusters. Young adults are centralized in regions with more quaternary sector jobs and public transit shares, and less manufacturing.